Reference and Inference in Conversation of Buyer and Seller - Devi Maharani Santika, I Dewa Ayu; Dian Andriyani, Anak Agung Ayu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
When people doing interaction, they will produce some utterances to deliver a certain meaning by using some language feature which can be in form of words or sentences. These language features enable the reader or speaker to identify something and the meaning that tries to be delivered must be inferred. This research is aimed at identifying reference and forming inferences from utterances spoken in some conversation between buyer and seller in some mini markets. The data were taken from 7 conversations of buyers and sellers. The utterances from that conversation, which are using some language features to determine the reference and recognize the inference to get the speaker meaning, were collected by note taking after hearing them when visiting some mini markets around Denpasar City. They were analyzed using the theory of inference from Yule (1996) supported by Cummings (2007) and Woods (2010) and also Halliday’s theory about context of analysis is used to obtain proper analysis. The analysis is presented descriptively since this research is a qualitative research. Generally, the results of this research show that references from the utterances are in the form of Noun phrase and the inferences are often made by the buyer as the listener since the utterances spoken by the sellers are short and full of implied meaning. Inference helped the buyer to take any action when they shopped. The contexts of the situation are also important to be noticed to form an inference from the interaction between the buyers and the sellers.